The Nexus Between Gross Domestic Product, Stock Market and Trade Openness: Evidence from Nepal - Phaju, Rajan (Quest Journal of Management and Social Sciences, 2022)
Background: The development of the stock market has a significant positive impact on economic growth and helps to effectively funnel savings and investment into the economy in ways that allow for the accumulation of capital. Stock market serves a crucial economic purpose by bringing investors and savers together. Similarly, trade openness increases efficiency in both static and permanent way. Ultimately it makes positive contribution in economic development. The causal relationship between the gross domestic product, the NEPSE index, and trade openness has been examined. Objective: To find out long run and short run relationship and the causal relationship among gross domestic product, Nepal stock exchange and trade openness, and whether there is causal relation among variables or not. Method: An Autoregressive distributed lag (ARDL) model is used in the analysis. The Engle Granger causality test, which demonstrates the direction of causality between the variables is also used. From the year 1994 to 2021 samples are taken. Results: Bound Test shows there is long run relationship among variables. Similarly, there is unidirectional causal relationship between gross domestic product and the Nepal stock market index. Implication: The results show that there is no meaningful relationship between GDP and trade openness. It is suggested that trade barriers be lowered and that international trade be promoted by reducing and simplifying processes. The reason for this must be low export quantities. Therefore, government must take action in this sector to encourage export and displace import. Additionally, the outcome demonstrates that there is no relationship between trade openness and the stock market. For Nepal's stock market to accept global investors, its regulations must be changed.